Analytical study of the performance of the offensive skills and their relationship to the difference in the order of women’s volleyball. - Mohammed, Hazim (Journal of Physical Education, 2015)
The research covered the five-door: Chapter One: contains the door on the front and the importance of research and touched on the volleyball game and includes the attacking skills , which includes transmitter and battery crushing and wall Alsdomchklh search in the analysis of attacking skills (transmitter , Aldharbb overwhelming , bulwark) with the order of teams participating in the League women’s volleyball 2013. Part II: This has touched the door to Alndharah studies related to the subject of the study included the terms of the basic skills in the game of volleyball offensive and defensive , and the importance of analysis in the game , as well as previous studies. Part III: research methodology and procedures Field Then addressed in this section to how to test the research methodology , the researcher used the descriptive approach style Relations connectivity to Mlomth with the nature of the research and how to choose the sample and Cat sample of four teams and the League for the two phases and the means to gather information and the tools and equipment used as well as steps to conduct research and how to design a form of observation and evaluation , and a main experiment as well as statistical methods. Part IV: Results , analysis and discussion This included the door to view and analyze and discuss their relationship with offensive skills arrange league teams as well as the differences in the performance of the offensive skills and their relationship to arrange league teams. If Adhrt results that there is a relationship between random and arranging skills offensive teams in the league for the women’s volleyball season in 2013 and has been discussing these results in a scientific manner supported by scientific sources. Part V: Conclusions and recommendations